A Novel ERF Transcription Factor, ZmERF105, Positively Regulates Maize Resistance to Exserohilum turcicum - Zang, Zhenyuan; Lv, Ying; Liu, Shuang; Yang, Wei; Ci, Jiabin; Ren, Xuejiao; Wang, Zhen; Wu, Hao; Ma, Wenyu; Jiang, Liangyu; Yang, Weiguang (Frontiers in Plant Science, 2020)
The ethylene response factor (ERF) plays a crucial role in plant innate immunity. However, the molecular function of ERF in response to Exserohilum turcicum (E. turcicum) remains unknown in maize. In this study, a novel ERF gene, designated as ZmERF105, was firstly isolated and characterized. The ZmERF105 protein contains an APETALA2/ETHYLENE RESPONSIVE FACTOR (AP2/ERF) domain and a conserved LSPLSPHP motif in its C-terminal region. ZmERF105 protein was exclusively localized to the nucleus. ZmERF105 expression responded to E. turcicum treatment. Yeast one-hybrid and transcription activity assays revealed that ZmERF105 is an activator of transcription and binds to GCC-box elements. Over-expression of ZmERF105 was shown to increase maize resistance against E. turcicum, and erf105 mutant lines displayed opposite phenotype. Moreover, the activities of superoxide dismutase (SOD) and peroxidase (POD) in the ZmERF105 over-expression lines were markedly higher than in the wild-type maize lines (CK) after infecion with E. turcicum, and were compromised in the erf105 mutant lines. Simultaneously, ZmERF105 over-expression lines enhanced the expression of several pathogenesis-related (PR) genes, including ZmPR1a, ZmPR2, ZmPR5, ZmPR10.1 and ZmPR10.2 after infecion with E. turcicum. In contrast, the expression of PR genes was reduced in erf105 mutant lines. Our work reveals that ZmERF105 as a novel player of the ERF network and positively regulates the maize resistance response to E. turcicum.